(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper examines the relevance of ethnopedagogical approaches in the context of innovative education. Ethnopedagogy, which integrates traditional knowledge and cultural values into educational practices, enhances student engagement and motivation by making learning more culturally relevant and relatable. It fosters inclusivity and equity by recognizing and valifying diverse cultural perspectives, thereby creating a more supportive and respectful learning environment. Furthermore, ethnopedagogical approaches develop critical thinking and intercultural competence, preparing students for global citizenship. These approaches also promote social justice by challenging Eurocentric educational models and addressing systemic inequities.